A Study Of Building Automation System (Bas)- A Case Study At The School Of Civil Engineering, Universiti Sains Malaysia - Mudzrab, Fitri Mahamad (Universiti Sains Malaysia, 2017)
The increase of luxury lifestyle has increased the demand of BAS due to increasing awareness about this technology that has transformed the building technology as well as the increase of safety and comfort to users. These significant changes have brought many changes to the structure of the building, systems, services, and management. The combination of these factors has led to the era of automatic and intelligent buildings. The advanced technology was created to establish a system of efficient energy usage and this aspect is basically used as a key objective for many countries. This dissertation's objective is to review the concepts of Building Automation System (BAS), determine the trends, and the factors that influence the need for and the growth of building automation at the School of Civil Engineering, USM. Besides, to statistically measure the extent of knowledge about BAS technology among the students at the School of Civil Engineering, USM. The study focussed on the aspects of BASs that are available at the School of Civil Engineering, Universiti Sains Malaysia (USM) with specific regard to the five aspects of Building Automation System that is heating ventilation and air conditioning (HVAC), lighting control system, fire and life safety control, security and access control, and building management system. The result shows that main factor that influences the trends of Building Automation System (BAS) at the School of Civil Engineering, USM is energy efficiency, As the current trends of BAS at the School of Civil Engineering, USM is in moderate trend, so the increases in adoption of BAS are important to reduce the problem of energy sources that facing great pressure due to energy demand is scaling higher from day to day.